ABOUT CASE ECTOPIC PREGNANCY AND OVARIAN CORPUS LUTEUM HEMOPERITONEUM MASS WITH BROKEN CONTRALATERAL - Jerí J., Arturo (2015)
This case reports associating a right ovarian ectopic pregnancy that meets the criteria for diagnosis Spiegelberg linked to the presence of contralateral corpus luteum rupture with massive hemoperitoneum, motivating an emergency laparotomy. The pathologic diagnosis replenished early-stage pregnancy in right ovary and corpus luteum rupture left.